Fungal Species Diversity in French Bread Sourdoughs Made of Organic Wheat Flour - Urien, Charlotte; Legrand, Judith; Montalent, Pierre; Casaregola, Serge; Sicard, Delphine (Frontiers in Microbiology, 2019)
Microbial communities are essential for the maintenance and functioning of ecosystems, including fermented food ecosystems. The analysis of food microbial communities is mainly focused on lactic acid bacteria, while yeast diversity is less understood. Here, we describe the fungal diversity of a typical food fermented product, sourdough bread. The species diversity of 14 sourdoughs collected from bakeries located all over France was analyzed. Bakeries were chosen to represent diverse bakery practices and included bakers and farmer-bakers. Both non-culture-based (pyrosequencing of Internal Transcribed Spacer 1 amplicons) and culture-based methods were used. While both identification methods were in agreement regarding the dominant yeast species of each sourdough, the ITS1 metabarcoding analysis identified an increased number of fungal in sourdough communities. Two third of the identified sequences obtained from sourdoughs were Saccharomycetales, mostly in the Kazachstania genus. No Saccharomycetales species was shared by all the sourdoughs, whereas five other fungal species, mainly known plant pathogens, were found in all sourdoughs. Interestingly, Saccharomyces cerevisiae, known as “baker’s yeast”, was identified as the dominant species in only one sourdough. By contrast, five Kazachstania species were identified as the dominant sourdough species, including one recently described Kazachstania species, Kazachstania saulgeensis and an undescribed Kazachstania sp. Sourdoughs from farmer-bakers harbored Kazachstania bulderi, Kazachstania unispora and two newly described Kazachstania species, while sourdough from bakers mostly carried Kazachstania humilis as the dominant species. Such yeast diversity has not been found in sourdoughs before, highlighting the need to maintain different traditional food practices to conserve microbial diversity.